Determinants of Turkey's foreign aid behavior. (May 2019) - Zengin, Hüseyin; Korkmaz, Abdurrahman
Abstract: This paper analyzes a hundred Turkish aid recipient countries in order to explore the determinants of Turkey's foreign aid behavior during the period 2005–2016. By estimating the model with the system-GMM estimator, it is demonstrated that Turkey is a regular donor whose amount of foreign aid is positively influenced by the export-based embeddedness of Turkish firms in the recipient countries. Recipients with low levels of per-capita income attract more Turkish aid. However, this income's effect diminishes in states that were formerly part of Ottoman territory. Recipient countries in an aid relationship with OECD-DAC members also receive more foreign aid from Turkey. In addition, Turkey disburses more foreign aid to recipient countries that can be classified as Turkic republics. Turkish foreign aid behavior is also motivated by Ottomanism, especially in the Balkans and Eastern Europe. Finally, and interestingly, although Islam has a considerable impact on attracting Turkish aid overall, this impact disappears in former Ottoman states and Turkic republics.